The Changes in the Laboratory Values During Administration of Commercially Available Ready-to-use Basal Solutions for Total Parenteral Nutrition - Kimura, Yasuhiro; Sato, Eiji; Kihira, Kenji; Kitaura, Teruaki; Fukuchi, Hiroshi; Miyake, Katsushi; Arai, Shigeaki; Sakai, Masahiko; Ikeda, Hiroaki (Iryo Yakugaku (Japanese Journal of Pharmaceutical Health Care and Sciences), 2001)
Some differences are seen in the concentrations of glucose and electrolytes between commercially available ready-to-use basal solutions for total parenteral nutrition (R-TPN). In this study, we investigated the effects of the long-term administration of Unicaliq®, which contains relatively higher concentrations of chloride ions than other R-TPNs, on the clinical laboratory values. One hundred and nineteen patients, who received Unicaliq® for more than four weeks at Hiroshima University Hospital, participated in this study. The laboratory values of chloride ion (Cl-) and blood urea nitrogen (BUN) significantly increased after receiving Unicaliq® for 2 weeks, but all levels, except for BUN, returned to the pretreatment levels after 4 weeks of administration. However, these changes were slight and all were within the normal ranges. No changes were observed in other laboratory values during the 4-week administration period. These results suggest that the clinical laboratory values are not affected by the long-term administration of Unicaliq®, at least up until 4 weeks.